2014
DOI: 10.1080/13572334.2014.943491
|View full text |Cite
|
Sign up to set email alerts
|

Budgetary Negotiations: How the Chilean Congress Overcomes its Constitutional Limitations

Abstract: Recent research suggests that the Chilean Congress is marginalised in the policymaking process, especially when setting the budget. This paper argues that previous studies have overlooked the fact that the legislature uses two amendment tools -specifications and marginal notes -to increase the national budget and reallocate resources within ministries. This behaviour contradicts the constitution, which only allows Congress to reduce the executive's budget bill. To test this empirically, a pooled two-stage time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In fact, Chilean presidents cannot unilaterally modify the status quo (Alemán and Navia, 2016). Recent studies find that the legislature has found additional ways to influence the lawmaking process (Arana Araya, 2015;Faúndez Caicedo et al, 2022). Using different methodologies and approaches, a few studies openly call into question the alleged existence of hyperpresidentialism in Chile (Martínez and Dockendorff, 2023;Mimica et al, 2023;Jaime-Godoy and Navia, 2023).…”
Section: Presidentialism and Legislative System In Chilementioning
confidence: 99%
“…In fact, Chilean presidents cannot unilaterally modify the status quo (Alemán and Navia, 2016). Recent studies find that the legislature has found additional ways to influence the lawmaking process (Arana Araya, 2015;Faúndez Caicedo et al, 2022). Using different methodologies and approaches, a few studies openly call into question the alleged existence of hyperpresidentialism in Chile (Martínez and Dockendorff, 2023;Mimica et al, 2023;Jaime-Godoy and Navia, 2023).…”
Section: Presidentialism and Legislative System In Chilementioning
confidence: 99%
“…Previous works have underlined the institutional design features conducive to executive-legislative bargaining and cooperation (Aninat et al 2006). In advancing their agendas, presidents have opted for cooperation and consensus building with the legislature more than confrontation (Siavelis 2002), especially on bills that require high voting thresholds (Aninat et al 2006), due to the informal structures of power in the lawmaking process (Arana Araya 2013;2015;Soto 2015b, 207).…”
Section: The Presidential Veto In Chilementioning
confidence: 99%
“…The MPs also need the political will to use them. An example of this was seen in Chili where the legislature amended the annual budget proposals of the executive, using formal and informal tools (Arana Araya, 2015).…”
Section: National Factorsmentioning
confidence: 99%